The EMT framework of reference for competences applied to translation: perceptions by professional and student translators - Chodkiewicz, Marta (The Journal of Specialised Translation, 2012)
In the past forty years, several attempts have been made at naming and defining the concept of translation competence, as well as at identifying its sub-types and organising them into comprehensive models. A recent contribution which draws on and expands earlier scholarly models is the European Master's in Translation (EMT) reference framework. This framework is worth noting since it was compiled at the request the EU, a major employer and stakeholder in the European translation industry, and serves as a prerequisite for universities which apply to be part of a prestigious network of EU-approved translation programmes. This paper reports a study investigating how the competences which are part of the framework are perceived by two groups of subjects: translation students, whose views have been shaped only by the academic environment, and professional translators, who additionally have some work experience. For this purpose a questionnaire was devised based on the EMT framework; it was completed by a group of current postgraduate translation students of the University of Surrey, one of whose translation programmes follows the framework, and a group of professional translators, most of whom are graduates of this university. The first goal of the study was to establish how relevant the respondents found particular competences for their (future) work as translators. The other goal was to examine to what extent the views of the two groups differed and to attempt to explain these differences. In addition, some differences were found between the perceptions of freelance and in‑house translators and were accounted for.